Multiplayerkit: um framework para o desenvolvimento de jogos multiplayer para dispositivos IOS - Sabino, João Paulo de Oliveira (2019)
This work presents MultiplayerKit, a framework that helps in the development of multiplayer games for iOS devices. The project, the architecture and the main functionalities implemented for the tool are detailed. Also presented are the results of usability tests with users who indicated a reasonable success in using the tool and from which it was possible to extract a list with improvements that can make the interaction more effective. As it is a free tool, it is expected that MultiplayerKit can be a viable alternative for small teams and projects of limited scope.